GAFATAR DAN DINAMIKA GERAKAN SOSIALNYA - Enkin Asrawijaya (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
Gafatar is a form of community upheaval in Indonesia in the current reform era. Issues surrounding the ideology and the attempts of treason case became the problem that caused Gafatar to lose the masses of the public. Gafatar has the concept of food self-sufficiency which is then implemented in a peasant movement as its criticism of the government. To explain the dynamics of the Gafatar social movement, used the theory of McAdam et al, about Political Opportunities, Mobilizing Structures, and Cultural Framings. The political opportunity arises from the distrust of government programs that have been offered to the people who are deemed to be ineffective. Mobilizing Structur Gafatar movement is manifested through the formation of the organization, forming a network of cooperation and collective action. While cultural framing, created through the issues addressed to Gafatar causing the formation of negative stigma in society.